La extradición ((Videoteca Jurídica))
Mesa redonda sobre la extradición vista desde las leyes mexicanas. Intervienen: Alonso Gómez Robledo, Emilio Rabasa, Loreta Ortiz, Rodolfo Cruz Miramontes, Víctor Carlos García Moreno, José Ramón Cossío, Carlos Bernal, Arturo Luis Cosío.